Pengembangan Budaya dan Iklim Sekolah Berbasis Kurikulum Merdeka Belajar - Tompul Tompul (Jurnal Syntax Transformation, 2022)
The presence of a new curriculum requires adaptation as well as a series of new plans and models. The education that will be received by students during learning and education in schools will create the term climate and school culture. School climate itself can be said as a pattern of behavior of school residents that reflects the norms and goals as well as values ​​and interpersonal relations as well as teaching and learning practices as well as organizational structure. In the end, the curriculum used will continue to develop and adapt to the times, including the emergence of an independent curriculum. This research uses qualitative research type. This research is a type of research by describing the results descriptively. Qualitative research is research that conducts reform research. This research was conducted because there has been no previous research so it is necessary to do research in order to find new research results. The results will be processed and a reduction technique will be carried out. Data can be displayed in a discourse. In this study, it can be used to analyze very deep issues. This independent curriculum actually has a very large impact and affects the culture and school climate. In school culture, the presence of strategies and ways that are carried out by schools on educational life will change. Previously, schools usually implemented learning strategies by focusing more on efforts to be able to develop students' academic potential more optimally and thoroughly. The new culture here exists by looking at and observing everything that exists to build new strategies to create a balance between each student's talents and interests that are developed and not only focused on a particular science.